The Making of an African Working Class : Politics, Law, and Cultural Protest in the Manual Workers Union of Botswana - Werbner, Pnina (Pluto Press, 2014)
Exploration of the formation of a distinctive working class identity among low-paid manual workers in Botswana.
Keywords: National Amalgamated Local & Central Government & Parastatal Manual Workers Union.; National Amalgamated Local & Central Government & Parastatal Manual Workers Union; Labor unions -- Botswana -- History.; Working class -- Botswana -- History.; Botswana -- Social conditions.; Botswana -- Politics and government.; Syndicats -- Botswana -- Histoire.; Travailleurs -- Botswana -- Histoire.; BUSINESS & ECONOMICS -- Labor.; POLITICAL SCIENCE -- Labor & Industrial Relations.; LAW -- Labor & Employment.; Labor unions; Politics and government; Social conditions; Working class; Botswana; Labor unions -- Industry. -- Botswana -- History.; Electronic books.; History